PENYUSUNAN LAPORAN KEUANGAN USAHA MIKRO KECIL DAN MENENGAH SESUAI SAK EMKMPADA WINDA CAKE CURUP - Paddery (Jurnal Ilmiah Raflesia Akuntansi, 2021)
Abstrack-The main objective of this research is to compile simple financial reports on Winda cake Curup to comply with the Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM).The method used in this research is quantitative descriptive method and data collection techniques are carried out using literature studies and field studies, the data used are primary data and secondary data with the object being analyzed is financial records for the period January to March 2020.The results of the research show that the preparation of reports on Winda cake Curup still uses simple reports consisting of financial reports, income statements and financial report notes, the authors suggest that Winda Cake company should immediately implement the financial reports that the authors have made based on SAK EMKM so that they can assist in retrieval. decisions to come.